(Azido-kN)bis-(di-2-pyridylamine)-copper(II) hexa-fluoro-phosphate and (azido-kN)bis-(di-2-pyridylamine)-copper(II) chloride tetra-hydrate - Sujittra Youngme (2018)
The two new title complexes, [Cu(N3)(dpyam)2]PF6 (dpyam is di-2-pyridylamine, C10H11N3), (I), and [Cu(N3)(dpyam)2]Cl·4H2O, (II), respectively, have been characterized by single-crystal X-ray diffraction. Both complexes display a distorted square-pyramidal geometry. Each Cu atom is coordinated in the basal plane by three dpyam N atoms and one azide N atom in equatorial positions, and by another N atom from the dpyam group in the apical position. In complex (I), the one-dimensional supra-molecular architecture is assembled via hydrogen-bonding inter-actions between the amine N atom and terminal azide N atoms and the F atoms of the PF6 - anion. For complex (II), hydrogen-bonding inter-actions between the amine N atom, the Cl- anion and water O atoms result in a two-dimensional lattice. © 2007 International Union of Crystallography.